96. Blink reflex intraoperative monitoring during microvascular decompression for hemifacial spasm: Our experience. Issue 1 (January 2015) - Simioni, V.; Sette, E.; Capone, J.G.; Cavallo, M.; Farneti, M.; Granieri, E.; Tugnoli, V.
<x xml:space="preserve">Abstract</x> Hemifacial spasm (HFS) is caused by vascular compression of the facial nerve at its root exit zone from the brainstem. Microvascular decompression (MVD) is a surgical treatment option that offers the prospect of a definitive cure for HFS. Intraoperative monitoring of abnormal muscle response has been used to predict MVD effectiveness. In patients with HFS Blink Reflex (BR) recorded in laboratory shows abnormal R1 diffusion in inferior facial muscles. BR has recently been introduced as a feasible technique during intraoperative monitoring (IOM) of facial nerve function. We evaluated intraoperative feasibility and modifications of BR during MVD for HFS in 8 patients. BR was recorded in 7/8 patients. R1 recorded from inferior facial muscles (orbicularis oris, mentalis muscles) disappeared in 3/7 patients, while it decreased in amplitude during surgery in 4/7 patients. HFS was completely resolved at early follow up evaluation (one week after surgery) in all patients with intraoperative loss of R1 from inferior facial muscles; in the other 4 patients HFS resolution was heterogeneous. Intraoperative BR monitoring can be a complementary technique during HFS surgery to optimize the MVD.